2016
DOI: 10.1063/1.4949524
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mach number on the efficiency of microwave energy deposition in supersonic flow

Abstract: The article is devoted to experimental and numerical studies of the efficiency of microwave energy deposition into a supersonic flow around the blunt cylinder at different Mach numbers. Identical conditions for energy deposition have been kept in the experiments, thus allowing to evaluate the pure effect of varying Mach number on the pressure drop. Euler equations are solved numerically to model the corresponding unsteady flow compressed gas. The results of numerical simulations are compared to the data obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
2
16
0
4
Order By: Relevance
“…From the experiment of Lashkov et al [12], which varied the size of an obstacle and the position of the discharge, it has been confirmed that a larger model is more influenced by the same microwave discharge. In subsequent studies [13], both numerical and experimental studies have shown that a decrease in the resistance, resulting from a microwave energy deposition, increases proportionally to the Mach number in the range from 1.6 to 8. Azarova et al [14] performed a numerical simulation to study the effects of symmetrical and asymmetrical deposition of microwave filament.…”
Section: Introductionmentioning
confidence: 96%
“…From the experiment of Lashkov et al [12], which varied the size of an obstacle and the position of the discharge, it has been confirmed that a larger model is more influenced by the same microwave discharge. In subsequent studies [13], both numerical and experimental studies have shown that a decrease in the resistance, resulting from a microwave energy deposition, increases proportionally to the Mach number in the range from 1.6 to 8. Azarova et al [14] performed a numerical simulation to study the effects of symmetrical and asymmetrical deposition of microwave filament.…”
Section: Introductionmentioning
confidence: 96%
“…Various types of plasma discharges have shown promising characteristics in different applications including flow control in aerodynamics [5][6][7], ignition and combustion in propulsion engineering [8][9][10][11][12][13], stabilization of flames [14][15][16][17]. Characteristic propane ignition and combustion times in the supersonic flow with Mach number 2 could be decreased up to factor 2-5 by plasma-assisted combustion [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic propane ignition and combustion times in the supersonic flow with Mach number 2 could be decreased up to factor 2-5 by plasma-assisted combustion [8,9]. Influence of the energy input of a microwave discharge on shock-wave structures and the flow around a body in a supersonic flow and the optimal discharge parameters to achieve the aerodynamic effect are studied in [6,7]. A model of an initiated microwave discharge in a linearly polarized wave beam is considered in [18].…”
Section: Introductionmentioning
confidence: 99%
“…Проделанные эксперименты показали значительное влияние плазмы СВЧ разряда на параметры набегающего потока, и оптимальные условия для приложений исследуются в новых работах [9][10][11][12][13][14][15].…”
Section: Introductionunclassified